Symbolist art theories : a critical anthology - Dorra, Henri, 1924-2002 (University of California Press, 1994)
Henri Dorra, in his comprehensive new book, presents the development and the aesthetic theories of the symbolist movement in art and literature. Included are writings (many never before translated or reprinted) by artists, designers, architects, and critics, along with Dorra's learned commentary. Fifty photographs of symbolist works complement his encyclopedic coverage. Dorra traces symbolism and its roots from artist to artist and critic to critic from the mid-nineteenth to the early twentieth century. The decorative arts and architecture are examined as well as painting and sculpture. The Arts and Crafts movement, art nouveau, the work of Eiffel in France, and that of Sullivan in the United States are well represented.